A method to estimate active drag over a range of swimming velocities which may be used to evaluate the stroke mechanics of the swimmer - Mason, B. R.; Formosa, D. P.; Toussaint, H. M. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: The high relationship between active and passive drag justified the following procedures. The aim was to develop a method to estimate the active drag of the swimmer over a range of swim velocities. The method developed relied upon having mean passive drag measures of the swimmer at various velocities, as well as the mean active drag value for the swimmer at their maximum swim velocity. METHODS: Eleven Australian team swimmers in freestyle participated in the study. The subjects completed three maximum swim velocity trials over a 10 m interval, to determine each subject`s maximum swim velocity. Three passive drag tests were performed at the swimmer`s maximum velocity. A series of passive drag trials was then completed over a range of 10 different tow velocities between 2.2 and 1.0 m/s. Finally, five active drag trials were completed at a five percent greater velocity than the swimmer`s maximum swimming velocity. These were used to compute the active drag at the swimmer`s maximum velocity. RESULTS: The exponential function as indicated was used to define the passive drag equation. where and are constants for a particular swimmer. The same equation was used to define active drag but here the constant was greater. DISCUSSION: In the active and passive drag equations, the value of the drag force was represented as an exponential function of swimming velocity. The rate of rise in the active and passive drag equations was represented by two separate constants. These constants may be used as indices to describe the individual swimmer`s capabilities. The constant in the equation for passive drag would represent an index of the swimmer`s innate physical characteristics such as size, shape and cross sectional frontal surface area. The lower the index, indicated a more efficient body shape for aquatics movement. The difference between the constant used in the active drag equation and that in the passive drag equation could be used as an index to represent the efficiency of the swimmer`s technique. These two indices may provide insight as to the capability of the swimmer to compete at various distance events. CONCLUSION: The present study demonstrated the importance of being able to generate an equation to represent a swimmer`s active drag over a range of velocities. This concept will provide insight as to the suitability of the individual to specific distance events, as well as, indicate the efficiency of the swimmer`s technique.